Evaluasi Distribusi BBM di Lingkungan Polri Dalam Mendukung Pelaksanaan Tugas Operasional Kepolisian Guna Mewujudkan Penguatan Pengawasan - Harvin Raslin (Jurnal Litbang Polri, 2022)
This research is expected to be information about the evaluation of fuel distribution in the Police environment in supporting the implementation of operational tasks to realize strengthening supervision. The purpose of this research is to identify and analyze the implementation of fuel planning and procurement systems in the Police environment, the implementation of fuel distribution, and the current fuel distribution supervision system, as well as formulate appropriate fuel governance in the Police environment. This research uses a mixed method of quantitative methods supported by qualitative methods. Respondents answered questionnaires via mobile phones online. Furthermore, qualitative data is in the form of a narrative that describes a certain reality or circumstances from the scope of research. Qualitative data collection is carried out by FGD with participants consisting of main officials and police members who are respondents. In the distribution of BBM, there are still some obstacles such as the similarity of planning documents from the previous year and minimal personnel certification. It is expected that the governance of distribution in the future can be more effective and efficient and the transfer of the use of paper forms on Ranjen and coupons into digital cards.